Analysis Of Crystallographic Patterns Of Iban Pua Kumbu - Liyana, Truna; Noria, Tugang; Norhunaini, Mohd Shaipullah; Nur Rasfina, Mahyan (Wolters Kluwer Health, 2022)
One of the famous traditional textiles in Sarawak is the Iban Pua Kumbu. This paper presents the crystallographic patterns, geometry concept and symmetry analysis present in the Iban Pua Kumbu patterns. This paper will also look at the colour-symmetrical patterns and motifs used in these textiles. The Ibans' weaving technique subtly incorporates geometric concepts using exquisite and precious designs. The Pua Kumbu of the Iban can be similarly classified according to the patterns displayed in the wallpaper and frieze. The current research findings could assist students to learn mathematics. In this study, samples comprising eight (8) repeated patterns were collected from field visits, museums in the Sarawak, and personal collections of scholars. From the findings, it shows that all Pua Kumbu patterns bear at least one of the seventeen crystallographic groups. Most of the Pua Kumbu motifs are symmetrical and those motifs is mathematically identified as a design. The Pua Kumbu contains decorative patterns whose relevance and imaginative portrayal are demonstrated by the intricacy of the creative process. Pua Kumbu weavers appear to have excellent memory skills, strong visual perception, and an innate aptitude for applying mathematics to their work.